Relationship between talent development, work environment, pay benefits and job satisfaction / Agassi Cantona Johnson - Johnson, Agassi Cantona (Faculty of Business and Management, 2019)
The objective of this study was to find out whether independent variables which were work environment, pay benefits and talent development have a positive relationship with the selected dependent variable, job satisfaction. The study also targeted respondents who currently working in construction sector which was employees of Sri Pengkalan Binaan’s group of employees been selected. The collected data of the study were analyzed using Statistical Package for Social Science (SPSS) software. The response rate of the respondents was 94.2% where 81 out of 86 respondents successfully return their questionnaires. Various types of analysis and tests had been conducted which is was consists of descriptive analysis, reliability test, correlation analysis, and multiple regression analysis. All of these analysis and tests was to study the data that have been collected. The study portrait that only one independent variable has a significant effect on job satisfaction which is working environment. While the other two independent variables (pay benefits and talent development) did not have significant effect on job satisfaction.